Islamic Financial Inclusion Index in Indonesia and its Correlation to Women's Quality of Life - Azqia, Hidayatul; Ali, Mohammad Mahbubi; Nurhasanah, Saniatun (SMART Insight, 2024)
This thesis discusses and provides an overview of the Islamic financial inclusion index in Indonesia and its correlation with women's quality of life. This study uses a descriptive quantitative approach with the method of calculating the Index of Sharia Financial Inclusion (ISFI). The data from this study uses secondary data obtained from the publications of the Financial Services Authority, the Central Statistics Agency and the Ministry of Child Protection and Women's Empowerment of the Republic of Indonesia. The study covers 33 provinces for the 2015-2020 period. The results of this study found that the level of Islamic financial inclusion in Indonesia was still relatively low at 0.105. Based on the observations, the provinces of DKI Jakarta and Nanggroe Aceh Darussalam, are the most superior provinces in measuring the Islamic financial inclusion index in this study, with the acquisition value of each province respectively 0.531 and 0.435. This study also found that the Islamic financial inclusion index (ISFI) has a positive relationship to women's quality of life (IPG). These results indicate that changes in the level of Islamic financial inclusion will result in changes in women's quality of life (IPG) in the same direction or if the ISFI index increases by one unit it will increase the GPA index by 7.811.